Involvement of a cyclic adenosine monophosphate–dependent signal in the diet‐induced canalicular trafficking of adenosine triphosphate–binding cassette transporter g5/g8. Issue 4 (30th June 2015) - Yamazaki, Yasuhiro; Yasui, Kenta; Hashizume, Takahiro; Suto, Arisa; Mori, Ayaka; Murata, Yuzuki; Yamaguchi, Masahiko; Ikari, Akira; Sugatani, Junko
<x xml:space="preserve">Abstract</x> The adenosine triphosphate–binding cassette (ABC) half‐transporters Abcg5 and Abcg8 promote the secretion of neutral sterol into bile. Studies have demonstrated the diet‐induced gene expression of these transporters, but the regulation of their trafficking when the nutritional status changes in the liver remains to be elucidated. Here, we generated a novel in vivo kinetic analysis that can monitor the intracellular trafficking of Abcg5/Abcg8 in living mouse liver by in vivo transfection of the genes of fluorescent protein‐tagged transporters and investigated how hypernutrition affects the canalicular trafficking of these transporters. The kinetic analysis showed that lithogenic diet consumption accelerated the translocation of newly synthesized fluorescent‐tagged transporters to intracellular pools in an endosomal compartment and enhanced the recruitment of these pooled gene products into the bile canalicular membrane in mouse liver. Because some ABC transporters are reported to be recruited from intracellular pools to the bile canaliculi by cyclic adenosine monophosphate (cAMP) signaling, we next evaluated the involvement of this machinery in a diet‐induced event. Administration of a protein kinase A inhibitor, N‐(2‐{[3‐(4‐bromophenyl)−2‐propenyl]amino}ethyl)−5‐isoquinolinesulfonamide, decreased the canalicular expression of native Abcg5/Abcg8 in lithogenic diet–fed mice, and injection of a cAMP analog, dibutyryl cAMP, transiently increased their levels in standard diet–fed mice, indicating the involvement of cAMP signaling. Indeed, canalicular trafficking of the fluorescent‐tagged Abcg5/Abcg8 was enhanced by dibutyryl cAMP administration. Conclusion: These observations suggest that diet‐induced lipid loading into liver accelerates the trafficking of Abcg5/Abcg8 to the bile canalicular membrane through cAMP signaling machinery. (Hepatology 2015;62:1215‐1226)